Ways to Develop Quick-Strength Qualities of Young Handball Players (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, technical and tactical training and fast-strength qualities of young handball athletes during the game are studied from a developmental perspective, focusing on its impact on both learning and physical well-being.